Building research capacity and relationships in schools: the consequences of involvement in 'Closing the Gap' - Childs, A; Fancourt, N (Routledge, 2017)
A critical factor in how teachers value research is the schools' institutional research culture, for instance, the extent to which it is open to organisational learning generally and experimentation and initiatives in particular; this is linked clearly to school leadership. The Closing the Gap (CtG) project demanded school leadership level involvement and indeed required schools to address the issue of being a control or intervention group only within the trials. The Alliance works with a range of strategic partners including Oakridge Teaching School in Westley, Harely Local Authority and a range of Higher Education Institutions, including Cavereley University and Eastridge University. The school development plan actions are conducted in teams, using evidence based research as a way of addressing school improvement priorities. The CtG has acted as a catalyst on engagement in and with research in schools and presents some challenges for further development of research-informed schools.